Dinaric Perspectives on TIMSS 2019 Teaching and Learning Mathematics and Science in South-Eastern Europe - Japelj Pavešić, Barbara; Koršňáková, Paulína; Meinck, Sabine (IEA Research for Education, 2022)
This open access book brings together national experts from across the Dinaric region to rigorously review IEA's Trends in International Mathematics and Science Study (TIMSS) 2019 grade four data to develop a multidimensional and culturally sensitive perspective on their TIMSS 2019 primary-level results. The Dinaric region, named after the Dinaric Alps, is located in South-eastern Europe, and stretches through Croatia, Bosnia and Herzegovina, Serbia, Montenegro, Kosovo[1], Albania, and North Macedonia. IEA's TIMSS has been an invaluable resource for monitoring international trends in mathematics and science achievement at grades four and eight since 1995. The TIMSS 2019 administration of the test to grade four students, provided a unique opportunity for analysis within shared regional settings and enabled the construction of this first report based on international study results from the region, prepared by the National Research Coordinators in collaboration with IEA. [1] This designation is without prejudice to positions on status and is in line with UNSCR 1244/1999 and the ICJ Opinion on the Kosovo declaration of independence.